2003
DOI: 10.1046/j.0306-5251.2003.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus dose requirement in renal transplant recipients is significantly higher when used in combination with corticosteroids

Abstract: Aims To evaluate the effect of corticosteroids on tacrolimus pharmacokinetics. Methods In a randomized trial, kidney transplant recipients were treated with tacrolimus and mycophenolate mofetil with either daclizumab ( n = 31) or 3 months of prednisone ( n = 34). Tacrolimus dose-adjusted predose concentrations ( C 0 ) at month 1-6 were compared between both groups and within the corticosteroid group before and after prednisone withdrawal. Results At month 1 the tacrolimus dose-adjusted C 0 in the corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 13 publications
4
43
0
Order By: Relevance
“…Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionsupporting
confidence: 79%
See 1 more Smart Citation
“…Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionsupporting
confidence: 79%
“…No difference in cyclosporine and tacrolimus dose requirement [49] Renal transplant patients T-129C, C1236T, G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus dose requirement in carriers of the 2677T/A alleles [44] Pediatric heart transplant patients G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus blood levels at 6 and 12 months [47] Japanese women T-129C -Increased placental P-glycoprotein expression levels [22] Caucasian volunteers C1236T + G2677T/A (Ala893Ser/Thr) + C3435T…”
Section: Impact Of Mdr1 Genetic Variation On Expression and Function mentioning
confidence: 99%
“…In an additional mixed-model analysis in which we adjusted for Tac assay by introducing a dummy variable as a random effect, the effect of CYP3A4 intron 6 genotype was still significant, both for the Tac daily dose (Ϫ20% for carriers of the T allele, P ϭ 0.007) and for the dose-adjusted C 0 (ϩ37% for T allele carriers, P Ͻ 0.001). Second, corticosteroids are known to influence Tac exposure (31,32 ). Given that corticosteroid tapering was recommended but not mandatory, the different centers may have used different corticosteroid regimens, which we cannot exclude from having influenced the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these we should mention first of all, the simultaneous immunosuppressive medication such as mycophenolate mofetil, where research shows increased serum levels of tacrolimus [14]. Corticotherapy may also represent a significant underlying factor, since it uses the same isoenzymes of cytochrome P 450 for byotransformation (CYP3A4), leading to a decrease of tacrolimus level in the blood, having a slight enzymatic inductor effect [15]. Another important element is the age of renal allograft, the patients age at the moment of transplant, the medication administered for other comorbidities such as calcium-channel blockers (felodipine) for the treatment of hypertension -4 patients from group 1 and 2 patients from group 2 [16]; theophylline for the treatment of asthma -1 patient from group 1 [17], ketoconazole, inhibitor of CYP3A4, for the treatment of mycotic infections -2 patients from group 1 and 1 patient from group 2 [18],the patients' diet (grapefruit juice, intake of pomelo, foods that may act as enzymatic inhibitors of CYP3A4) [19,20], CYP3A4 polymorphism [21].…”
Section: Discussionmentioning
confidence: 99%